Notes on three species of Gigartinaceae (Rhodophyta) from Peruvian coast - Calderón, Martha (2010)
Gigartinaceae family has been under constant taxonomic changes due to the high morphologic variability of the species. Conventionally its taxonomy has been based in external morphology; nevertheless, recent morphologic studies, supported in molecular studies, have delimited the genus of this family on the basis of cystocarp development and the tetrasporangia. The vegetative and reproductive structures of three common species of the family present in the coast of Peru are described and commented: Chondracanthus chamissoi, Mazzaella denticulata and Chondrus canaliculatus.